2022
DOI: 10.1136/bmjopen-2022-063903
|View full text |Cite
|
Sign up to set email alerts
|

Acute and repeated impact of sweeteners and sweetness enhancers in solid and semi-solid foods on appetite: protocol for a multicentre, cross-over, RCT in people with overweight/obesity – the SWEET Project

Abstract: IntroductionIntake of free sugars in European countries is high and attempts to reduce sugar intake have been mostly ineffective. Non-nutritive sweeteners and sweetness enhancers (S&SEs) can maintain sweet taste in the absence of energy, but little is known about the impact of acute and repeated consumption of S&SE in foods on appetite. This study aims to evaluate the effect of acute and repeated consumption of two individual S&SEs and two S&SE blends in semisolid and solid foods on appetite an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…v. water). The status of these trials was reported (per 13 February 2024) to be 'completed' (ClinicalTrials.gov identifiers NCT05010408, NCT04609657 and NCT04226911 (44) ), or with estimated completion dates in 2023 (ClinicalTrials.gov identifier NCT04633681 (45) ), 2024 (ClinicalTrials.gov identifiers NCT02591134 (46,47) , NCT04816955 (48) , NCT05672017, NCT04497974 (49) , NCT05684757 and NCT05932329) or 2025 (ClinicalTrials.gov identifiers NCT04567108 and NCT04079855). Most of the studies have exposure durations of several weeks or months and include only adult participants.…”
Section: Ongoing (Registered) Trials and Reviewsmentioning
confidence: 99%
“…v. water). The status of these trials was reported (per 13 February 2024) to be 'completed' (ClinicalTrials.gov identifiers NCT05010408, NCT04609657 and NCT04226911 (44) ), or with estimated completion dates in 2023 (ClinicalTrials.gov identifier NCT04633681 (45) ), 2024 (ClinicalTrials.gov identifiers NCT02591134 (46,47) , NCT04816955 (48) , NCT05672017, NCT04497974 (49) , NCT05684757 and NCT05932329) or 2025 (ClinicalTrials.gov identifiers NCT04567108 and NCT04079855). Most of the studies have exposure durations of several weeks or months and include only adult participants.…”
Section: Ongoing (Registered) Trials and Reviewsmentioning
confidence: 99%